New record of slipper lobster Thenus indicus Leach, 1816 (Crustacea: Decapoda: Scyllaridae) from Bangladesh waters - Ahmed, Md Sagir; Datta, Sujan Kumar; Saha, Tonmoy; Antu, Durjoy Raha; Barua , Anindita; Ahmed, Sumaiya (Dhaka University Journal of Biological Sciences, 2023)
Slipper lobster Thenus indicus Leach, 1816 (Crustacea: Decapoda: Scyllaridae) has been recorded for the first time from Cox’s Bazar coast of the Bay of Bengal. The species was taxonomically identified by using the traditional morphometric method which was further validated by molecular approach based on partial cytochrome c oxidase subunit I (COI) and 16S rRNA gene sequences (DNA barcodes). The key characteristics of this species are spotless pereiopods, 1st pereiopod merus width less than 7% of carapace length, and 3rd pereiopod merus length more than 45% of carapace length. Dhaka Univ. J. Biol. Sci. 32(1): 11-19, 2023 (January)